Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Terhadap Produk Rabbani di Bunker Rabbani Pucang Surabaya - Paramitha, Mariska Pradnya; Hasib, Fatin Fadhilah (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to identify factors affecting consumer buyer decision to buy Rabbani products in Bunker Rabbani Pucang Branch Surabaya, amid burgeoning hijab trend fashion and competitive pressure from other retailers of moslem clothing products. In our study we employed quantitative approach, which followed by analysis using exploratory analysis factor. The sample population that we studied comprised of female customers buying Rabbani products in the above retailer, which we surveyed by using simple random sampling. The primary data collection is conducted in two stages: pre-test and main test, whereas secondary data are obtained elsewhere from literature. The pre-test was carried out by posing the questionnaire to 30 respondents. The result of pre-test is subsequently used as instrument indicator for main test which involving 91 respondents. From our investigation we obtained three factors behind consumer buyer decision to buy Rabbani products in the store used as case study: factor of product types, factor of price and store location, and factor of store promotion. Based on this result we thus provide suggestion to Rabbani store to keep up product attribute existence amid burgeoning hijab trend fashion and competitive pressure from other retailers of moslem clothing products.